2017
DOI: 10.1111/nep.12748
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress participates in inflammation‐accelerated, lipid‐mediated injury of human glomerular mesangial cells

Abstract: These data provide evidence that ER stress participates in inflammation associated with lipid-induced injury of HMCs. Modulation of ER stress may be a novel therapeutic approach for combating lipid-induced injury of HMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Moreover, Zofia et al confirmed that podocytes are the major IL‐1β‐secreting cell among kidney cells, and NLRP3 inflammasome activation is main molecular mechanism of maturation and secretion of IL‐1β. In a previous study, we showed that IL‐1β aggravates lipid‐induced podocyte and mesangial cell injury during PNS by disrupting SREBP2‐SCAP‐LDL receptor signalling and inducing endoplasmic reticulum stress This supports the notion that IL‐17A induces podocyte injury by inducing secretion of IL‐1β via activation of the NLRP3 inflammasome. However, the conclusion was mainly confirmed by IL‐17A‐induced podocyte injury model in vitro, and there was still lack of adequate direct reference to clinical kidney diseases.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, Zofia et al confirmed that podocytes are the major IL‐1β‐secreting cell among kidney cells, and NLRP3 inflammasome activation is main molecular mechanism of maturation and secretion of IL‐1β. In a previous study, we showed that IL‐1β aggravates lipid‐induced podocyte and mesangial cell injury during PNS by disrupting SREBP2‐SCAP‐LDL receptor signalling and inducing endoplasmic reticulum stress This supports the notion that IL‐17A induces podocyte injury by inducing secretion of IL‐1β via activation of the NLRP3 inflammasome. However, the conclusion was mainly confirmed by IL‐17A‐induced podocyte injury model in vitro, and there was still lack of adequate direct reference to clinical kidney diseases.…”
Section: Discussionsupporting
confidence: 73%
“…Researchers found that lipotoxicity induced ER stress via the protein arginine methyltransferase 1 (PRMT1), which exacerbated MC apoptosis. Interestingly, Yang et al [ 69 ] proved that inflammation accelerates lipid-induced MC injury through ER stress. Hence, strategies to mediate the expression of PRMT1 can be applied to prevent or limit DN.…”
Section: Roles Of Er Stress In Various Renal Cells In Dnmentioning
confidence: 99%
“…CKD is involved with glomeruli [7, 8], tubules [9, 10], and interstitial tissue around the glomeruli and tubules [11]. CKD often results in glomerular injury because of the destruction of glomerular structure caused by high-level inflammatory cells [12, 13]. The result will prevent blood flow, resulting in the decrease in urine output and accumulation of uremic toxin.…”
Section: Introductionmentioning
confidence: 99%